2009
DOI: 10.1080/00365520802699260
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous luminal nitric oxide exacerbates esophagus tissue damage in a reflux esophagitis model of rats

Abstract: Exogenous luminal nitric oxide greatly exacerbated the tissue damage of reflux esophagitis. Diffusion of the luminal nitric oxide into the adjacent superoxide-enriched inflamed tissue of the esophagus could lead to the production of the highly toxic agent peroxynitrite, thus causing exacerbation of the esophageal damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 47 publications
4
34
0
Order By: Relevance
“…3,4 Free oxygen radicals or reactive oxygen species (ROS) play an important role in the acute stage of esophageal burn and reflux esophagitis. [5][6][7] ROS, in particular superoxide anion (O 2 À ), play an important role in the pathogenesis of esophagitis induced by acid and pepsin. 7 The role of oxidative stress in MTX-induced small intestinal toxicity has been researched and found that animals that received N-acetylcysteine or tungsten showed a decreased production of ROS and decreased myeloperoxidase activity.…”
mentioning
confidence: 99%
“…3,4 Free oxygen radicals or reactive oxygen species (ROS) play an important role in the acute stage of esophageal burn and reflux esophagitis. [5][6][7] ROS, in particular superoxide anion (O 2 À ), play an important role in the pathogenesis of esophagitis induced by acid and pepsin. 7 The role of oxidative stress in MTX-induced small intestinal toxicity has been researched and found that animals that received N-acetylcysteine or tungsten showed a decreased production of ROS and decreased myeloperoxidase activity.…”
mentioning
confidence: 99%
“…Ishiyama et al have shown that co-administration of sodium nitrite and ascorbic acid increased reflux-induced esophageal damage fourfold to fivefold in mice, while neither of the agents alone could do so. Their data suggested that this damage was mediated by the interaction of nitric oxide and superoxide species giving rise to the highly noxious peroxynitrite [15]. In another study, Ito et al demonstrated that DIS, a characteristic histological finding of reflux esophagitis, can be induced in rat esophageal epithelium by exposing it to sodium nitrite and acid but not acid alone [16].…”
Section: Discussionmentioning
confidence: 97%
“…Recent ecologic data have linked high nitrate content of drinking water to increased prevalence of acid regurgitation [14]. In addition, animal studies have shown that when reflux is induced in mice, they develop significant esophagitis only when fed a diet containing nitrates [15]. It has also been shown that dilated intercellular space (DIS), a basic histological characteristic of the lower esophagus in GERD, is induced by nitrates and acid, but not by acid alone [16].…”
Section: Introductionmentioning
confidence: 97%
“…34,35 It was reported that exogenous luminal NO exacerbates tissue damage in a RE model of rats. 36 In esophageal cells, iNOS was up-regulated by common reflux constituents, leading to NO production. 37 Diffusion of the luminal NO into ), 3-NT (C) levels, and MDA levels (D) of esophagus.…”
Section: Discussionmentioning
confidence: 99%